Coronary blood flow, metabolism, and function in dysfunctional viable myocardium before and early after surgical revascularisation. Issue 11 (14th October 2004) - Alamanni, F; Parolari, A; Repossini, A; Doria, E; Bortone, F; Campolo, J; Pepi, M; Sisillo, E; Naliato, M; Bigi, R; Biglioli, P; Parodi, O
Abstract : Objectives: To assess the link between perfusion, metabolism, and function in viable myocardium before and early after surgical revascularisation. Design: Myocardial blood flow (MBF, thermodilution technique), metabolism (lactate, glucose, and free fatty acid extraction and fluxes), and function (transoesophageal echocardiography) were assessed in patients with critical stenosis of the left anterior descending coronary artery (LAD) before and 30 minutes after surgical revascularisation. Setting: Tertiary cardiac centre. Patients: 23 patients (mean (SEM) age 57 (1.7) years with LAD stenosis: 17 had dysfunctional viable myocardium in the LAD territory, as shown by thallium-201 rest redistribution and dobutamine stress echocardiography (group 1), and six had normally contracting myocardium (group 2). Results: LAD MBF was lower in group 1 than in group 2 (58 (7) v 113 (21) ml/min, p < 0.001) before revascularisation and improved postoperatively in group 1 (129 (133) ml/min, p < 0.001) but not in group 2 (105 (20) ml/min, p  =  0.26). Group 1 also had functional improvement in the LAD territory at intraoperative echocardiography (mean regional wall motion score from 2.6 (0.85) to 1.5 (0.98), p < 0.01). Oxidative metabolism, with lactate and free fatty acid extraction, was found preoperatively and postoperatively in both groups; however, lactate and free fatty acid uptake increased after revascularisation only in group 1. Conclusions: MBF is reduced and oxidative metabolism is preserved at rest in dysfunctional but viable myocardium. Surgical revascularisation yields immediate perfusion and functional improvement, and increases the uptake of lactate and free fatty acids.